2013
DOI: 10.1021/ol4014602
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3-Mediated Cyclization of [60]Fullerene with N-Benzhydryl Sulfonamides under High-Speed Vibration Milling Conditions

Abstract: The FeCl3-mediated reaction of [60]fullerene with N-benzhydryl sulfonamides afforded C60-fused indane derivatives using the high-speed vibration milling technique. A possible reaction mechanism involving the unprecedented FeCl3-mediated homolytic C-N bond cleavage of N-benzhydryl sulfonamides is proposed. The electrochemistry of the obtained C60-fused indanes was also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 25 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…C 60 -Fused indanes 65 could be synthesised by the reaction of fullerene 61 with N -benzhydryl sulphonamides 64 and FeCl 3 in a ball mill ( Scheme 19 ). 85 C 60 -Fused indanes (yield: 15–41%) could be obtained within 1 hour under ball milling, whereas no product was formed using solution-based methods ( Scheme 19 ).…”
Section: Different Reaction Products or Different Reactivitymentioning
confidence: 99%
“…C 60 -Fused indanes 65 could be synthesised by the reaction of fullerene 61 with N -benzhydryl sulphonamides 64 and FeCl 3 in a ball mill ( Scheme 19 ). 85 C 60 -Fused indanes (yield: 15–41%) could be obtained within 1 hour under ball milling, whereas no product was formed using solution-based methods ( Scheme 19 ).…”
Section: Different Reaction Products or Different Reactivitymentioning
confidence: 99%
“…The most likely reason is that the possibility for the close contact of two neighboring molecules of 3a to dimerize under solvent-free conditions is much higher than that under liquid-phase conditions [ 15 ]. This result provided another example to showcase the uniqueness of altering the reaction pathway by the mechanochemical protocol [ 15 , 17 , 18 ]. It should be noted that the expected product shown in Scheme 1 still could not be obtained from the reaction of 1a with CaC 2 , NaCl, Oxone, and Na 2 CO 3 ; compound 3a was obtained in essentially the same yield as that without CaC 2 after stirring for 1 h ( Scheme 1 ), while a similar complex mixture with no obvious predominant product was observed for the reaction with or without CaC 2 after 24 h. These results indicated that CaC 2 did not participate in the present liquid-phase reaction, and a longer reaction time could not afford 2a , 3a , or any other meaningful product.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wang et al reported the reaction of [60]fullerene (C 60 ) and KCN under high-speed vibration ball milling (HSVM) for 30 min to unexpectedly afford fullerene dimer C 120 even after quenching with trifluoroacetic acid (TFA) [15], while the same reaction in a mixture of 1,2-dichlorobenzene (ODCB) and N,N-dimethylformamidal (DMF) reported earlier by Wudl and coworkers afforded a different fullerene product, C 60 H(CN) [16]. Another example was the mechanochemical reaction of C 60 and N-benzhydryl sulfonamides in the presence of FeCl 3 to give fulleroindanes, which could not be obtained in ODCB or 1,1,2,2-tetrachloroethane (TCE) solution at 120 • C [17]. A more recent example reported by Bolm, Hernández, and coworkers was the reaction of aldehydes with amines and CaC 2 under ball-milling conditions to give 1,4-diamino-2-butynes [18].…”
Section: Introductionmentioning
confidence: 99%
“…[71] For example, the FeCl 3 -mediated reaction of [60]fullerene with N-benzhydryl sulfonamides afforded C 60 -fused indane, in as olvent-free mechanochemical reactionm edia (with high-speed vibration milling). [72] Analogously to indane derivatives, different fullerene heterocyclic compounds can be prepared by using radicalmediated iron(III) cyclization reactions. Dioxanes and dioxepanes, [73] lactones, [74] dioxolanes, [75] oxazoles, [76] oxazolidinone, [77] and oxazolidine fullerene derivatives [78] have all been prepared by using stoichiometric amounts of iron(III) salts.…”
Section: Radical Cyclization Reactionsmentioning
confidence: 99%